Strategies for Fostering Prosocial Behavior: A Mixed Methods Study in Indonesian Islamic Schools - Hady, M. Samsul; Aziz, Rahmat; Nuqul, Fathul Lubabin; Mahpur, Mohammad; Nashori, Fuad; Alribdi, Nada Ibrahim (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This article aims to analyze the influence of the Islamic school environment on students' prosocial behavior, with an emphasis on the integration of religious values in learning strategies and school policies. Design/methods/approach – This study used a sequential explanatory mixed-method design involving 445 students, four principals, and eight teachers from four Islamic junior high schools. The quantitative stage used structured questionnaires to assess prosocial behavior, school climate, and classroom learning practices. The qualitative stage involved interviews with principals and teachers to provide contextual understanding. Findings – Quantitative results show that the school atmosphere explains 27.2% of the variation in students' prosocial behavior (R² = .272). The most influential factors are peer relationships (β = .173), sense of belonging (β = .148), and interpersonal justice (β = .123). For classroom practices, positive teaching (β = .353) and teacher encouragement (β = .113) made significant contributions. Qualitative findings support these results, with teachers and principals citing programs such as 5S, study groups, and Friday donations as effective ways to foster empathy, cooperation, and concern among students. Research implications/limitations – This study highlights the importance of an Islamic-based environment in encouraging prosocial behavior, although the findings may not be generalized to non-Islamic educational contexts. Originality/value – This study offers valuable insights into the intersection between religion and education, and contributes to strategies for developing prosocial behavior in Islamic school.